ANALYSIS OF CAPITAL MARKET REACTIONS TO THE ANNOUNCEMENT OF THE PPATK POLICY ON THE BLOCKING OF DORMANT ACCOUNTS IN 2025(A Case Study of LQ45 Banking Stocks Listed on the Indonesia Stock Exchange) - Anak Agung Sagung Wulan Maharani; Ni Putu Ayu Darmayanti (Adisam Publisher, 2026)
The reaction of the capital market to a particular event is an important aspect for investors to observe in making future investment decisions, as it may influence fluctuations in stock market prices. This study aims to examine the capital market reaction resulting from the 2025 announcement of the Financial Transaction Reports and Analysis Center (PPATK) policy regarding the blocking of dormant accounts, which may affect investor confidence in banking companies and investment activities in Indonesia. This study constitutes a semi-strong form efficient market hypothesis test employing the event study method with an 11-day observation period on banking sector companies included in the LQ45 Index on the Indonesia Stock Exchange, selected using purposive sampling. The expected return in this study was calculated using the market-adjusted model. The hypothesis testing method applied was the Wilcoxon signed-rank test. The results indicate that there were no significant differences in the average values of cumulative abnormal return and trading volume activity before and after the announcement of the PPATK policy on the blocking of dormant accounts in 2025. These findings suggest that the announcement of the PPATK policy is consistent with the semi-strong form of market efficiency theory, indicating that no investors were able to consistently obtain abnormal returns because the market adjusted rapidly to the announcement information. Furthermore, the capital market did not perceive the dormant account blocking policy as relevant information capable of altering investment decisions in banking stocks.